Importance of energy efficiency standards and labels for household refrigerators in Malaysia - Lau, H.M (Universiti Malaysia Sarawak (UNIMAS), 2008)
Refrigerator-freezers, being one of the major electricity consuming household appliances in Malaysia have become a target for improvement of energy consumption. Until now, Malaysia has not set any standards or labeling for refrigerator-freezers. The objectives of this study are to develop a set of energy efficiency standards and labels for household refrigerator-freezers. By referring to ISO (International Standard Organization) Test Standards, a series of experimental investigations have been conducted towards fifteen units of refrigerator-freezers with different capacities and trademarks. From the experimental data, a baseline standard has been developed by statistical approach. A 10% saving line has been developed from the baseline standard. Three types of energy saving labels have been designed and a survey has been conducted towards these labels among the consumers. From the survey response, a comprehensive energy guide label for refrigerator-freezers has been proposed in this project. It has been estimated that 40869.594 MWh of electricity energy could be saved per year by introducing energy efficiency standards to refrigerator-freezers. With the mandatory implementation of energy efficiency standards for refrigerator-freezers, it has been estimated that at least 10% of pollution issues would be reduced in Malaysia.